2006
DOI: 10.1038/ng1738
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic CLOCK-BMAL1 binding to multiple E-box motifs drives circadian Dbp transcription and chromatin transitions

Abstract: Mammalian circadian rhythms are based on transcriptional and post-translational feedback loops. Essentially, the activity of the transcription factors BMAL1 (also known as MOP3) and CLOCK is rhythmically counterbalanced by Period (PER) and Cryptochrome (CRY) proteins to govern time of day-dependent gene expression 1 . Here we show that circadian regulation of the mouse albumin D element-binding protein (Dbp) gene involves rhythmic binding of BMAL1 and CLOCK and marked daily chromatin transitions. Thus, the Dbp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
512
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 527 publications
(564 citation statements)
references
References 31 publications
46
512
0
Order By: Relevance
“…2f) was performed as previously described 61 . Primers for the E-box-containing region in the mouse Ho-1 promoter were: 5 -TGCAACAGCAGCGAGAAC-3 (forward), 5 -GAAACTC TGGAGGCGACTG-3 (reverse) and 5 -FAM-CCACCACGTGACCCGCGTAC-TAMRA-3 (probe).…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
See 1 more Smart Citation
“…2f) was performed as previously described 61 . Primers for the E-box-containing region in the mouse Ho-1 promoter were: 5 -TGCAACAGCAGCGAGAAC-3 (forward), 5 -GAAACTC TGGAGGCGACTG-3 (reverse) and 5 -FAM-CCACCACGTGACCCGCGTAC-TAMRA-3 (probe).…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
“…Cross-linking, chromatin preparation and chromatin immunoprecipitation were performed as described in ref. 61, with modifications. Cells were sonicated on ice for 15 s five times at a 50% setting, then centrifuged for 10 min (16,000g).…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
“…Using the circadian transcription factor albumin D-site binding protein (Dbp) gene as a model system, Stratmann et al (2010) uncovered a mechanism that partially uncouples the expression of this gene from the circadian oscillator. The Dbp gene has been identified as a direct target for rhythmic BMAL1 and CLOCK binding (Kiyohara et al, 2008;Ripperger and Schibler, 2006;Ripperger et al, 2000;Yamaguchi et al, 2000). In their study, Stratmann et al (2010) have identified a special function of a BMAL1 binding site in the promoter region of the Dbp gene to adjust the phase of its expression according to the photoperiod.…”
Section: Transcriptional Network Of the Hepatic Circadian Oscillatormentioning
confidence: 99%
“…At the moment, there is good evidence of chromosomal topological alteration that links the cyanobacterial clock to its molecular outputs, whereas we tend to assume that eukaryotic clock-controlled genes are regulated by rhythmic activity of specific transcriptional factors. However, we might find in time that regulation of chromosomal remodeling is also very important in the regulation of transcription by eukaryotic clocks; indeed, recent evidence suggests that the mammalian clockwork does just that (Etchegaray et al, 2003;Ripperger and Schibler, 2006;Doi et al, 2006). In eukaryotes, activation and repression of transcription are often associated with modifications to histones (e.g., phosphorylation, methylation, or acetylation) that condense/decondense chromatin.…”
Section: Concluding Remarks/implications For Other Circadian Systemsmentioning
confidence: 99%